Empire's crossroads : a history of the Caribbean from Columbus to the present day - Gibson, Carrie, 1976- (New York : Atlantic Monthly Press, 2014)
Traces the story of the coveted area from the northern rim of South America up to Cuba, exploring its history from the arrival of Columbus through colonialism to the present, offering a panoramic view of this complex region.
In October 1492, an Italian-born, Spanish-funded navigator discovered a new world, thousands of miles across the Atlantic Ocean. In Empire's Crossroads, Carrie Gibson, unfolds the story of the Caribbean, from Columbus's first landing on the island he named San Salvador to today's islands-- largely independent, but often still in thrall to Europe and America's insatiable desire for tropical luxuries. From the early years of settlement to the age of sugar and slavery, during which vast riches were generated for Europeans through the enforced labour of millions of enslaved Africans, to the great slave rebellions of the eighteenth and nineteenth centuries and the long, slow progress towards independence in the modern era, Gibson offers a vivid, panoramic view of this complex and contradictory region. From Cuba to Haiti, from Jamaica to Trinidad, the story of the Caribbean is not simply the story of slaves and masters, but of fortune-seekers, tourists, scientists and pirates. It is not only a story of imperial expansion-- European and American-- but also of life as it is lived in the islands, both in the past and today.
A passage to the Indies -- Steeping stones to the New World -- Pirates and Protestants -- Sugar -- The rise of slavery -- A world at war -- Haiti, or, The beginning of the end -- Cuba and the contradictions of freedom -- Banana wars and global battles -- The road to independence -- The Cold War in the tropics -- Island life -- Import/export -- Invented paradise -- Timeline : key events in the Caribbean -- Gazetteer : The Caribbean (and surroundings).
"First published in Great Britain in 2014 by Macmillan, an imprint of Pan Macmillan"--Title page verso.
Includes bibliographical references (pages 369-376) and index.
Keywords: Caribbean Area -- History; Caribbean Area -- Social conditions; Social history; Caribbean Area; History